Combination of cetuximab with chemoradiation, trastuzumab or MAPK inhibitors: mechanisms of sensitisation of cervical cancer cells - Meira, D D (Nature Publishing Group, 2009)
BACKGROUND: Cervical cancer (CC) annually kills 288 000 women worldwide. Unfortunately, responses to chemoradiation are partial and are of short duration. As anti-EGFR monoclonal antibodies sensitise tumours, we investigated cetuximab's toxicity plus chemoradiation on CC cells, which express different EGFR levels. METHODS: EGFR, HER2, AKT and MAPK expression and phosphorylation status were determined by western blotting. Cytotoxicity was assessed by MTT or clonogenic assays (CA) in cell lines treated with cetuximab alone or in combinations. RESULTS: Cetuximab with cisplatin and radiation achieved maximum cytotoxic effects for A431, Caski and C33A cells (high, intermediate and low EGFR expression, respectively) in CA. Cetuximab efficiently decreased MAPK and AKT phosphorylation in A431 cells but slightly less in Caski and C33A cells. To check whether further EGFR, HER2 or MAPK inhibition would improve cetuximab's cytotoxicity, we combined it with an EGFR tyrosine kinase inhibitor (TKI), trastuzumab or a MEK1/2 inhibitor (PD98059). In Caski, but not in C33A cells, cetuximab cooperated with the TKI, reducing cell survival and AKT and MAPK phosphorylation. However, cetuximab with trastuzumab or PD98059 reduced survival and MAPK phosphorylation of both cell lines. CONCLUSION: Our data suggest that cetuximab combined with chemoradiation, trastuzumab or MAPK inhibitors has useful applications for CC treatment, independently of EGFR expression.